2005
DOI: 10.1210/en.2004-1003
|View full text |Cite
|
Sign up to set email alerts
|

Differential Estrogen Receptor Expression in Autoimmune Myasthenia Gravis

Abstract: Myasthenia gravis (MG) is an autoimmune disease associated with thymic hyperplasia and is much more prevalent in women than men. In this study we investigated potential changes in estrogen receptor (ER) expression in thymic hyperplasia. We first quantified by real-time PCR the relative expression of ER alpha and ER beta in normal thymus and found that the ER beta to ER alpha ratio was inverted in thymocytes (8.6 +/- 1.2), compared with thymic epithelial cells (0.18 +/- 0.05). The ER transcript number gradually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
3
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 53 publications
2
47
3
1
Order By: Relevance
“…Conversely, male androgens have been shown to relieve SLE in female patients [88] . Myasthenia gravis is another predominantly female autoimmune disease which has been shown to involve increased ER ␣ and ER ␤ on T cells and ER ␣ on thymocytes, indicating a potential role of estrogen in the pathogenesis of myasthenia gravis patients [89] . Reduced levels of androgens and increased estrogen have also been associated with inflammation in rheumatoid arthritis; however, changes in these hormones do not initiate flares as readily as in SLE [90] .…”
Section: Gender Bias and Autoimmunitymentioning
confidence: 99%
“…Conversely, male androgens have been shown to relieve SLE in female patients [88] . Myasthenia gravis is another predominantly female autoimmune disease which has been shown to involve increased ER ␣ and ER ␤ on T cells and ER ␣ on thymocytes, indicating a potential role of estrogen in the pathogenesis of myasthenia gravis patients [89] . Reduced levels of androgens and increased estrogen have also been associated with inflammation in rheumatoid arthritis; however, changes in these hormones do not initiate flares as readily as in SLE [90] .…”
Section: Gender Bias and Autoimmunitymentioning
confidence: 99%
“…An * indicates a significant difference at p <0.05. In our studies, we also observed that Foxp3, which is a specific marker for regulatory activity (78) (192,193 (127,195). However, studies have…”
Section: Estrussupporting
confidence: 67%
“…They may act as immunosuppressors as well as immunostimulators, and the balance between these two processes seems to be dependent upon steroid hormones levels. The higher incidence of AID in women seems to be linked to influence of sex steroid hormones on autoimmunity, as ER and PR were reported to be expressed also on some types of immune cells [5,25,26]. This may partly explain the higher incidence of AID noted in woman.…”
Section: Discussionmentioning
confidence: 98%